1997
DOI: 10.1002/(sici)1096-9918(199706)25:7/8<548::aid-sia269>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Multi-method Analysis of the Metal/Electrolyte Interface: Scanning Force Microscopy (SFM), Quartz Microbalance Measurements (QMB), Fourier Transform Infrared Spectroscopy (FTIR) and Grazing Incidence X-ray Diffractometry (GIXD) at a Polycrystalline Copper Electrode

Abstract: The successful application of various in situ and ex situ analytical techniques has been demonstrated at the buried interface between a metal and an electrolyte. Scanning force microscopy (SFM), electrochemical quartz microbalance measurements (EQMB), grazing incidence x‐ray diffractometry (GIXD), Fourier transform infrared spectroscopy (FTIR) in the specular reflection absorption mode and electrochemical charge measurements proved complementary in the characterization of a polycrystalline copper electrode in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…In the case of electropolishing, previous research has shown that if current is reversed between anodic and cathodic potentials, the surface is smooth [17]. In this case, material removal rates could be negligible.…”
Section: Cyclic Potentialmentioning
confidence: 98%
“…In the case of electropolishing, previous research has shown that if current is reversed between anodic and cathodic potentials, the surface is smooth [17]. In this case, material removal rates could be negligible.…”
Section: Cyclic Potentialmentioning
confidence: 98%
“…Studies on the copper oxide passive films using different characterization methods have revealed that the composition of the copper oxide passive films depends on many variables such as solution conditions (Ref [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have been published on the passive behavior of copper and its alloys (Ref [14][15][16][17][18][19], there is still lack of knowledge on the effect of ARB process on the passive behavior of the oxide film formed on copper and its alloys. Indeed, the microstructure which is also influenced by the forming process can affect the passive film formation and its behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this passive film forms B Arash Fattah-Alhosseini a.fattah@basu.ac.ir 1 Department of Materials Engineering, Bu-Ali Sina University, Hamedan 65178-38695, Iran an efficient barrier against the metal dissolution. During the last decade, the composition of the passive films has been studied by using different surface characterization analysis [6][7][8][9]. However, the extensive number of researches has been focused on the passivation behavior of copper and its alloys [1][2][3][4][5][6][7][8][9][10], little paper has been published on the semiconducting behavior of the passive films formed on these alloys [10].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have already been reported to explain the properties and mechanism of the passive films on copper and its alloys [1][2][3][4][5][6][7][8][9][10]. However, little information about the effect of pH on the semiconductive behavior of the passive film formed on brass alloys was available.…”
Section: Introductionmentioning
confidence: 99%